Dual inhibition of PI3K and mTOR by VS-5584 suppresses thrombus formation. (3rd April 2018) - Später, Thomas; Müller, Isabelle; Eichler, Hermann; Menger, Michael D.; Laschke, Matthias W.; Ampofo, Emmanuel
Abstract: VS-5584 is a highly selective dual kinase inhibitor which suppresses phosphatidylinositol 3-kinase (PI3K) and mammalian target of rapamycin (mTOR) activity. Because these kinases are crucially involved in primary hemostasis, we herein investigated the effect of this compound on thrombus formation in vitro and in vivo . Pretreatment of washed platelets (WP) or platelet-rich plasma (PRP) with VS-5584 inhibited the agonist-induced activation of surface glycoprotein complex (GP)IIb/IIIa and the upregulation of P-selectin. This was associated with a significantly reduced formation of platelet-leukocyte aggregates (PLA). VS-5584 further attenuated platelet aggregation and adhesion after agonist stimulation. In contrast, endothelial expression of intercellular adhesion molecule (ICAM)-1 and vascular cellular adhesion molecule (VCAM)-1 and secretion of von Willebrand Factor (vWF) were not affected by the dual kinase inhibitor. In vivo, VS-5584 inhibited photochemically induced thrombus formation as shown by a significantly prolonged time to complete vessel occlusion when compared to vehicle-treated controls. This was associated with an elevated tail vein bleeding time, indicating a potential hemorrhagic risk in VS-5584-treated mice. Taken together, these novel findings demonstrate that VS-5584 is a potent inhibitor of primary hemostasis targeting multiple platelet functions.